サプリメント類の使用状況とその問題点 - Shibata Soichi; 阿部 宏子; 池田 将英; 井上 忠夫; Sakamoto Yasunori; Fujii Hiroyuki; 船木 文子; 宮澤 祐輝; 厚田 幸一郎 (Iyakuhin Johogaku, 2010)
Object: A multicenter survey was conducted to investigate the status of use of supplements and related problems in patients with diabetes mellitus.Methods: A questionnaire was mailed to institutions where members of the Drug Information Section, Tokyo Hospital Pharmacists Association, worked, and hospitalized patients with diabetes mellitus were surveyed with a questionnaire.Results: The response rate of the questionnaire was 85%, and 22 patients reported taking supplements.  The most common motivation to purchase supplements was a recommendation from an acquaintance, followed by a recommendation from a family member and TV. Only 9.1% of the patients consulted healthcare professionals when purchasing supplements.  The patients who did not follow the dosage and administration instructions and those who were not aware of precautions regarding proper use accounted for 31.8% and 63.6%, respectively.  The proportion of patients who did not inform their physicians about the use of supplements was 65.2%, and 4.5% reported some health damage (rash).Conclusion: Our results revealed that supplements were used without careful consideration and were not administered properly, suggesting that scientific evaluation of efficacy and safety was warranted in future studies.  It is important for pharmacists to actively collect information on patient use of supplements and share the information within the medical team.